Effective long-term control of Echinococcus multilocularis in a mixed rural-urban area in southern Germany - König, Andreas (PLoS One, 2019)
Effective preventive strategies are available to control Echinococcus multilocularis in foxes in order to reduce the human infection risk. Reduction of E. multilocularis prevalence in foxes was achieved in various studies by distributing praziquantel-containing bait by hand or by aircraft in either rural or settlement areas. Here, an integrated approach is described from southern Germany (district of Starnberg). Baseline data were obtained in winter 2002/03, when the prevalence rate in the project area was 51%. Between December 2005 and December 2011, air distribution of bait in agricultural and recreational areas was combined with distribution by hand in towns and villages, in order to cover the entire fox population, with a bait density of 50 pieces / km(2) (baiting area: 213 km(2)). In addition, a control area without anthelmintic treatment was selected. Prevalence was reduced in the baiting area to 1% by March 2007. Subsequently, from 2007 to the end of 2011, prevalence rates remained at a low level with 2.4% (2007), 2.4% (2008), 2.6% (2009), 1.2% (2010) and 0.0% (2011). In the un-baited control area the prevalence rates remained high, ranging from 19.6% to 35.1% with an average of 27.3%. During the 6 years of anthelmintic treatment, differences between baiting and control areas were highly significant (P<0.001). In the suburban and urban parts of the study area prevalence could be reduced to less than 1%, i.e. to a level below the limit of detection, which was maintained even after the measures had been discontinued. The applicability and effectiveness of anthelmintic baiting was therefore confirmed even for a heavily settled and fragmented landscape, which posed challenges for practical application of the control measures. The cost of the project ranged between € 1.70 and € 2.00 per inhabitant of the baiting area per year.